HUBUNGAN TINGKAT PENGETAHUAN DAN PERSEPSI IBU TENTANG KB SUNTIK 3 BULAN DENGAN TINGKAT KECEMASAN MENGHADAPI GANGGUAN MENSTRUASI DI PUSKESMAS BAKTIYA KABUPATEN ACEH UTARA - Wahyuni, Rita (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2023)
Many factors that influence causing anxiety include knowledge and perception. Knowledge is a factor that can affect the mother's mindset and negative perceptions of mothers about 3-month injectable contraceptives, increasing anxiety in dealing with menstrual disorders caused by the use of injectable contraceptives. This study aimed to determine the relationship between the level of knowledge and perceptions of mothers about 3-month injections with anxiety-facing menstrual disorders at the Baktiya Health Center, North Aceh Regency. This type of research is analytic with a cross-sectional study design, with a sample of 32 people from the total population. This research was conducted from 10 to 18 August 2017 with the method of distributing questionnaires. Data processing was carried out by editing, coding, tabulating, processing, and cleaning processes with univariate and bivariate methods using the chi-square test. The results of the univariate analysis showed that most of the mothers' knowledge was not good at opening 20 people (63%), most of the negative mothers' perceptions opened 18 people (56%), and most of the mothers experienced anxiety in facing 17 people (54%) while the results Bivariate analysis found that there was a significant relationship between mother's knowledge of 3-month injections of family planning and anxiety levels in dealing with menstrual disorders with a p-value of 0.001 and there was a significant relationship between mother's perception of 3-month injections of family planning with a mother's level of anxiety facing menstrual disorders with a p-value of 0.002. It is hoped that respondents will be able to increase their knowledge and provide a positive perception of the effects of using 3-month injectable contraception.